2021
DOI: 10.3390/ijerph182312666
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Career Firefighters’ Mental Health Impacts and Priorities

Abstract: Firefighters’ perceptions of mental health can inform management. This qualitative study explored Canadian career firefighters’ experiences, needs, and research priorities with respect to mental health. Thirty-nine career firefighters (33 men, 6 women) of different ranks and geographic locales were interviewed using a semi-structured interview guide. The interviews were recorded, transcribed, and qualitatively analyzed using thematic analysis within an interpretive description approach. Firefighters reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(52 reference statements)
3
5
0
Order By: Relevance
“…Stigma was a major personal moderator that acted as a barrier to discussing mental health with others, which supports prior literature findings 19,20 . Study findings correspond with the findings by MacDermid et al 25 on Canadian firefighters who reported stigma toward mental health is perceived as a sign of weakness. To no surprise being a male-dominant profession, stigma toward mental health is prevalent in firefighters.…”
Section: Discussionsupporting
confidence: 89%
“…Stigma was a major personal moderator that acted as a barrier to discussing mental health with others, which supports prior literature findings 19,20 . Study findings correspond with the findings by MacDermid et al 25 on Canadian firefighters who reported stigma toward mental health is perceived as a sign of weakness. To no surprise being a male-dominant profession, stigma toward mental health is prevalent in firefighters.…”
Section: Discussionsupporting
confidence: 89%
“…Although the precise reason for impaired sleep quality may vary according to the jurisdiction studied, previous work has drawn attention to factors such as longer shifts and frequent emergency calls 3,44 . Regardless of its underlying cause, however, sleep disturbances can have a profound influence on the mental health of those in the fire service; for example, poor sleep quality has been associated with PTSD symptoms 45 and insomnia has been linked to clear elevations in the risk of both anxiety and depression 46 …”
Section: Discussionmentioning
confidence: 99%
“…3,44 Regardless of its underlying cause, however, sleep disturbances can have a profound influence on the mental health of those in the fire service; for example, poor sleep quality has been associated with PTSD symptoms 45 and insomnia has been linked to clear elevations in the risk of both anxiety and depression. 46 Along with identifying potential psychosocial stressors within the fire service, we also observed certain factors that seemed to influence the experience of these stressors. For example, we found that participants who engaged in regular physical activity each week reported lower levels of both work-related and general life stress.…”
Section: Discussionmentioning
confidence: 99%
“…Firefighters’ work stressors may involve performing risky work task frequently in unstable, unfamiliar work zones with infectious/chemical hazards as well as long-lasting (24 h) shifts with rapid reaction periods between rest and emergency response (MacDermid et al 2021 ). Due to the specific nature of the work of firefighters, a high level of stress during workdays was noted (Santo de Oliveira et al 2012 ) and the severity of experienced stress increased with years of service (Santo de Oliveira et al 2012 ; Makara-Studzińska et al 2020 ).…”
Section: Airway and Systemic Inflammation In Firefightersmentioning
confidence: 99%